Gender Dynamics in Access to Justice in Afghanistan - World Bank (World Bank, Washington, DC, 2018)
Afghanistan has a multitude of complementary, competing, and at times conflicting spaces for rule-setting and dispute resolution; state laws, Shari'a, and customary practices and norms are applied and enforced in varying situations, by state as well as non-state justice institutions. State justice institutions are those which represent the central government and the formal legal system. Non-state justice institutions include a range of both traditional and new community organizations, such as shuras (local councils), among others. Even significant individual positions in communities can represent non-state justice institutions, as can be the case for mullahs. This study looks at the gender dynamics of access to justice services in Afghanistan. It examines the intersecting spaces of state and non-state institutions and their respective bodies of law and norms to gain a better understanding of how they affect the choices that women make in resolving disputes through those institutions. By investigating barriers hindering women's access to justice services, identifying the most common disputes or cases that women and men bring before justice institutions, examining justice-seeking behaviors of women and men, and documenting levels of satisfaction with the process and its outcomes, the study aims to provide Afghan and international policy makers and program designers with quantitative evidence to devise approaches that address gender-based inequities in women's access to justice and justice outcomes. Another contribution of this study is to inform the World Bank-financed Justice Service Delivery Project (JSDP), which is aimed at improving access to justice by supporting both state and non-state justice institutions.